DO ENVIRONMENTAL TAXES PAY OFF? THE IMPACT OF ENERGY AND TRANSPORT TAXES ON CO2 EMISSIONS IN TRANSITION ECONOMIES (The South East European Journal of Economics and Business, 2018)
In this paper we investigate the impact of environmental taxes on CO2 emissions in the context of emerging market economies. An attempt has been made to identify what role environmental policy and specific tax policy measures play in understanding the relationship between economic development and environmental degradation. The empirical analysis covers ten Central and Eastern European countries in the period from 1995 to 2015. The latest data on environmental taxes are available only from 1995. We contribute to recent literature in two respects. First, we study this relationship within a dynamic framework in which we take into account the issues of serial correlation and endogeneity in the regressors due to the cointegration relationship. Specifically, we rely on the fully-modified least squares (FM-OLS) estimation technique to model the long-term relationship between income and carbon-dioxide emissions. Second, this paper advances our understanding on the effectiveness of tax policy measures in curbing CO2 emissions, on which we have scarce empirical evidence. The results of this analysis provide rather strong evidence in support of an inverted U-shaped relationship between economic growth and the environment. However, environmental taxes do not seem to be effective in modifying the behaviour of economic agents and in protecting the environment. The results are robust to different models.